Ghost movies in Southeast Asia and beyond: narratives, cultural contexts, audiences - Bräunlein, Peter J.; Lauser, Andrea (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2016)
"Ghost Movies in Southeast Asia and Beyond explores ghost movies, one of the most popular film genres in East and Southeast Asia, by focusing on movie narratives, the cultural contexts of their origins and audience reception. In the middle of the Asian crisis of the late 1990s, ghost movies became major box office hits. The emergence of the phenomenally popular "J-Horror" genre inspired similar ghost movie productions in Korea, Thailand, Taiwan, Hong Kong, the Philippines and Singapore. Ghost movies are embedded and reflected in national as well as transnational cultures and politics, in narrative traditions, in the social worlds of the audience, and in the perceptual experience of each individual. They reflect upon the identity crises and traumas of the living as well as of the dead, and they unfold affection and attraction in the border zone between amusement and thrill, secular and religious worldviews. This makes the genre interesting not only for sociologists, anthropologists, media and film scholars, but also for scholars of religion"--